Evaluation of peptides release using a natural rubber latex biomembrane as a carrier - Miranda, M. C.R. [UNESP] (2018)
The biomembrane natural (NRL—Natural Rubber Latex), manipulated from the latex obtained from the rubber tree Hevea brasiliensis, has shown great potential for application in biomedicine and biomaterials. Reflecting the biocompatibility and low bounce rate of this material, NRL has been used as a physical barrier to infectious agents and for the controlled release of drugs and extracts. The aim of the present study was to evaluate the incorporation and release of peptides using a latex biomembrane carrier. After incorporation, the release of material from the membrane was observed using spectrophotometry. Analyses using HPLC and mass spectroscopy did not confirm the release of the antimicrobial peptide [W6]Hylin a1 after 24 h. In addition, analysis of the release solution showed new compounds, indicating the degradation of the peptide by enzymes contained in the latex. Additionally, the release of a peptide with a shorter sequence (Ac-WAAAA) was evaluated, and degradation was not observed. These results showed that the use of NRL as solid matrices as delivery systems of peptide are sequence dependent and could to be evaluated for each sequence.